Regulation effects of Trigonella foenum-graecum seed extract on a mouse model of allergic asthma - Shamsadin Athari; Mansoor Keshavarz; Mahmood Khodadoost; Maryam Hamzeloo-Moghadam; Alireza Abbassian; Rasool Choopani (Institue of Medicinal Plants, ACECR, 2021)
Background: Trigonella foenum-graecum L. (fenugreek) seeds have a long history of treating allergic asthma known as "Rabv" in Persian medicine. The protective effects of fenugreek on asthma have been noted in Persian medicine texts. Objective: The aim of the present study was to investigate the protective effects of aqueous fenugreek seed extract (AFSE) on the reduction of Th2 cytokines via decreasing the levels of mRNA expression of Th2 cytokines in bronchoalveolar lavage fluid (BALF). Methods: 28 female Balb/c mice were divided into four groups of seven animals. Negative and positive control groups received Phosphate-buffered saline and ovalbumin (OVA), respectively. The remaining two groups were firstly sensitized with OVA to induce asthma and then received Theophylline and AFSE. Thereafter, the mRNA expressions of Th2-type interleukins (IL-4, IL-5, and IL-13) and mucin5 as well as the concentrations of IL-5, IL-13, and IL-33 in BALF samples were measured and pathological alterations of lung tissues were analyzed. Results: AFSE treatment of Balb/c mice significantly decreased the number of eosinophils, the mRNA expressions of IL-4, IL-5, IL-13, and mucin5 and the concentrations of IL-5, IL-13, and IL-33 in their BALF specimens. It also considerably prevented peribronchial and perivascular inflammations, mucus hypersecretion, and goblet cell hyperplasia in lung tissues in comparison to OVA-sensitized mice. Conclusion: The present study demonstrated that the aqueous fenugreek seeds extract could be an alternative medication for the treatment of allergic asthma.